2018
DOI: 10.1371/journal.pone.0208842
|View full text |Cite
|
Sign up to set email alerts
|

Predicting return to work after acute myocardial infarction: Socio-occupational factors overcome clinical conditions

Abstract: ObjectivesReturn to work after acute myocardial infarction (AMI), a leading cause of death globally, is a multidimensional process influenced by clinical, psychological, social and occupational factors, the single impact of which, however, is still not well defined. The objective of this study was to investigate these 4 factors on return to work (RTW) within 365 days after AMI in a homogeneous cohort of patients who had undergone an urgent coronary angioplasty.ParticipantsWe studied 102 patients, in employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 33 publications
3
32
0
2
Order By: Relevance
“…This is consistent with previous findings showing a beneficial association between educational level and living with a partner with return to work. [16][17][18]20 Regarding gender differences, what we observed was consistent with the majority of previous findings, suggesting that women have lower rates of returning to work and longer sickness absences than men. 17,20,22 Dreyer et al and Cauter et al, however, did not find gender differences in their study after adjustment for other characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous findings showing a beneficial association between educational level and living with a partner with return to work. [16][17][18]20 Regarding gender differences, what we observed was consistent with the majority of previous findings, suggesting that women have lower rates of returning to work and longer sickness absences than men. 17,20,22 Dreyer et al and Cauter et al, however, did not find gender differences in their study after adjustment for other characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…15 In previous international studies of employed patients, 86-93% of the patients were found to have returned to work one year after acute MI. [16][17][18][19] However, detachment is present; in a Danish nationwide registerbased study almost a quarter of MI patients reported to quit working one year after they successfully returned to work. 17 This demonstrates the importance of long-term follow-up when measuring return-to-work rates after cardiovascular revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between anxiety and RTW diminished after controlling for depression, further indicating the major role of depression [15]. Similarly, a recent observational study [16] concluded that lower selfreported depression scores were predictive of early RTW. Psychological co-morbidities were stronger predictors of RTW, when compared to disease-related factors.…”
Section: Relevant Barriers/facilitators For Vocational Reintegrationmentioning
confidence: 91%
“…Stendardo et al found that a lower value of depression score increase the probability of a quicker return to work in patients after acute myocardial infarction. [ 25 ] Van der Kemp et al showed that depressive symptoms were associated with return to work after mild-to-moderate stroke. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%